Relation between soluble CD36 and dietary fatty acid composition in metabolic syndrome patients: Relationship Between CD36 and Dietary Fatty Acids - Mataraci Değirmenci, Duygu; Özdemir, Özlem; Fisunoğlu, Mehmet (Progress in Nutrition, 2022)
Background and aim: The CD36 fatty acid receptor, known as the scavenger receptor, is expressed in many cells and tissues. Dietary fatty acids are thought to play a role in the pathogenesis of metabolic disorders such as obesity, insulin resistance, and atherosclerosis. This study aimed to determine the relationship between soluble CD36 (sCD36) fatty acid receptors and dietary fatty acids in individuals with metabolic syndrome.Methods: This study included 33 patients with metabolic syndrome and 32 healthy individuals aged 18-65 years. The participants' sociodemographic characteristics, biochemical parameters, anthropometric measurements, type of dietary fat, fatty acid pattern, and amount of fat consumed were recorded. The sCD36 fatty acid receptor levels in individuals were analyzed.Results: Blood pressure and biochemical measurements (fasting glucose, HbA1c, insulin, HOMA-IR, triglyceride, total cholesterol, HDL, LDL, AST, ALT, and CRP) of individuals with metabolic syndrome were higher than those of the control group (p0.05). Individuals with metabolic syndrome had lower olive oil, higher corn oil and tail oil consumptions (p0.05). No correlation was observed between the sCD36 receptor levels and dietary fatty acid type in individuals with metabolic syndrome (p>0.05).Conclusions: Soluble CD36 level is not a possible biomarker for metabolic syndrome owing to its similar levels in these patients.